Biochemical markers of connective tissue in the pathogenesis of gastroenteritis in dogs and cats - Morozenko, Dmytro; Vashchykv, Yevheniia; Kononenko, Nadiia; Zakhariev, Andriy; Seliukova, Nataliia; Berezhnyi, Dmytro; Gliebova, Gliebova; Chikitkina, Valentyna (ScienceRise: Biological Science, 2022)
The aim: to analyze and establish the pathogenetic role of biochemical markers of the state of connective tissue in diseases of the stomach and intestines in dogs and cats. Materials and methods. The research was carried out by the method of analysis of sources of scientific literature (PubMed, Elsevier, electronic resources of the V. I. Vernadskyi National Library), because of which a scheme of the pathogenesis of gastroenteritis in dogs and cats with the participation of connective tissue biopolymers was created. Results. In dogs and cats, the issue of the use of biochemical markers for the diagnosis of diseases of the stomach and intestines has not yet been fully clarified. It is known, that in dogs and cats, lymphocytic-plasmacytic enteritis is histologically determined by fibrosis of the intestinal wall, but biochemical tests for the diagnosis of this condition are not given. Among the biochemical markers of inflammatory bowel disease, tumor necrosis factor, C-reactive protein and microalbumin were identified. Although C-reactive protein was elevated in a greater number of diseased animals, this increase was insignificant. Other tests also did not show high diagnostic informativeness. Several stages can be identified in the pathogenesis of alimentary gastroenteritis in dogs and cats. First, the irritating components of food act on the mucous membrane of the stomach and disrupt its secretory and motor functions, which causes gastritis. Thus, the use of indicators of the state of connective tissue in the diagnosis of intestinal diseases in dogs can be used to assess the degree of the inflammatory process. Conclusions. According to the results of the analysis, it was established, that the development of the inflammatory process in the stomach and intestines causes an increase in the content of glycoproteins in the blood serum of cats and dogs, and a decrease in synthetic processes in the liver is accompanied by a decrease in the concentration of glycosaminoglycans (GAG) in the blood serum of sick animals. It should be noted, that this decrease has peculiarities: in dogs, the content of total chondroitin sulfates remained at the level of clinically healthy animals, while the concentration of total GAG decreased. In cats, on the contrary, the content of total chondroitin sulfates decreased, and the fractional composition of GAG remained unchanged. The level of excretion of oxyproline and uronic acids in the urine of animals with gastroenteritis did not change, which indicates the absence of catabolism of collagen and proteoglycans with gastroenteritis